2021
DOI: 10.1089/bfm.2021.0082
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cell-Mediated Immune Response in Colostrum from Women Diagnosed Positive for SARS-CoV-2

Abstract: Objective: To evaluate the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in colostrum from women who tested positive for the virus. Methods: Between March and September 2020 we obtained bilateral colostrum samples collected on spot cards within 48 hours of delivery from 15 new mothers who had previously tested positive for SARS-CoV-2. Four of 15 women provided liquid colostrum, which was used for validating results obtained from spot cards. Archived bilateral colostrum samples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Subsequent steps followed the protocol for detection of RBD-specific immunoglobulins. 19 The neutralization assay was performed using a V-PLEX SARS-CoV-2 Panel 6 multiplex assay by Mesoscale Discovery (K15436U). The assay quantitatively measures antibodies in the sample that can inhibit the interaction of spike and its variants with ACE2.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent steps followed the protocol for detection of RBD-specific immunoglobulins. 19 The neutralization assay was performed using a V-PLEX SARS-CoV-2 Panel 6 multiplex assay by Mesoscale Discovery (K15436U). The assay quantitatively measures antibodies in the sample that can inhibit the interaction of spike and its variants with ACE2.…”
Section: Methodsmentioning
confidence: 99%
“…On average, the proportion of sIgA1 in the milk proteins of COVID-19 colostrum was 8.6 times greater than in the Ctrl colostrum (Figure 2D), thus indicating that the mothers’ responses to the infection and additional adaptive immunological protection for the infants from viruses may be introduced through the gastrointestinal or respiratory tract. Indeed, it has been reported that a portion of sIgA present in milk from COVID-19 patients were RBD-specific 53,54 . Such protection may be further strengthened by other adaptive immunity-related proteins that appear in higher abundances in COVID-19 colostrum than in Ctrl colostrum (Figure 2F).…”
Section: Discussionmentioning
confidence: 99%
“…In a disease state where SARS-CoV-2 is mucosally-acquired, we and others find the immune response mounted is primarily IgA 19,[24][25][26][27] . This is seen for one of the three vaccinated women in our study who also previously tested positive for SARS-CoV-2.…”
Section: Covid-19 Mrna Immunization In Milk From Lactating Womenmentioning
confidence: 92%
“…The copyright holder for this preprint this version posted October 14, 2021. ; https://doi.org/10.1101/2021.10.12.21264890 doi: medRxiv preprint COVID-19 mRNA immunization in milk from lactating women 10 Levels of SARS-CoV-2 RBD-specific immunoglobulins were measured as previously described 19 . For detection of total immunoglobulins, 96-well plates were coated with anti-IgA (α-chain specific) or anti-IgG (H+L specific) capture antibodies at 1 μg/mL (Jackson ImmunoResearch Laboratories, Inc.).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 1 more Smart Citation